Long-lasting consequences of the European crisis - Juan F. Jimeno (European Central Bank (ECB), 2015)
The Great Recession and the subsequent European crisis may have long-lasting effects on aggregate demand, aggregate supply, and, hence, on macroeconomic performance over the medium and long-run. Besides the fact that financial crisis last longer and are succeeded by slower recoveries, and apart from the hysteresis effects that may operate after episodes of long-term unemployment, the combination of high (public and private) debt and low population and productivity growth may create significant constraints for monetary and fiscal policies. In this paper I develop an OLG model, one earlier used by Eggertsson and Mehrotra (2014) to rationalize the "secular stagnation hypothesis", to show how high debt, and low population and productivity growth may condition the macroeconomic performance of some European countries over the medium and long-run.
Keywords: E20; E43; E52; E66; 330; inter-generational transfers; natural rate of interest; population and productivity growth; secular stagnation; zero lower bound